Fabrication of the amphiphilic hyperbranched poly(ether amine)@graphene (hPEA‐AN@G) hybrid assemblies by ball milling. Issue 4 (13th August 2021) - Li, Jin; Ma, Xiaodong; Su, Zhilong; Yin, Jie; Jiang, Xuesong
Abstract: Organic–inorganic hybrid assembly is a very attractive means for constructing complex functional materials. Here, a simple method for the preparation of amphiphilic hybrid graphene nanosheets (hPEA‐AN@G) is developed via the in situ hybrid assembly of anthracene‐ended hyperbranched poly(ether amine) (hPEA‐AN) and graphene by ball milling graphite in aqueous solution with hPEA‐AN. The amphiphilic hPEA‐AN, consisting of hydrophilic hPEA chains and electron‐rich π‐conjugated aromatic AN capped on the periphery, not only interacts strongly with graphene nanosheets and water molecules but also endows the hybrid hPEA‐AN@G assemblies with hydrophilic surfaces and functional groups. The concentration of the resulting few‐layered hPEA‐AN@G is as high as 3.5 mg mL –1 . Moreover, the total interaction energy ( V T ) of hPEA‐AN@G is V T, max  = 4.2 meV nm –2 calculated according to the classical Derjaguin–Landau–Verwey–Overbeek theory, as high as 16 800 eV for a 2 μm × 2 μm graphene flake, suggesting a high stability of the hPEA‐AN@G assemblies. The as‐prepared hPEA‐AN@G can be redispersed well in several organic solvents including N, N ‐dimethylformamide, 1, 4‐dioxane, acetone and ethanol for more than 3 months. The superior performance and convenient fabrication make this method very promising for the production of graphene nanosheets on a large scale in both aqueous and organic solution. © 2021 Society of Industrial Chemistry. Abstract : Fabrication of hybrid graphene nanosheets via ball‐milling exfoliation of graphite in the aqueous phase.